Preparation and Characterization of Biodegradable Microspheres Containing Sertraline Hydrochloride - Laith H. Samein; Ahmed A. Hussein; Alaa A. Abdulrasool; Jabar A. Faraj (College of Pharmacy University of Baghdad, 2017)
Four batches of sertraline HCl microspheres were prepared using a poly (D-L-lactide-co-glycolide) (PLGA) polymer ( Mw. 9, 27, 30 and 83 KDa) as  a delivery system. The microspheres were prepared by a dispersion/solvent extraction-evaporation method and characterized for drug loading by UV, particle size by laser diffractometry and surface morphology by scanning electron microscopy (SEM). The in vitro sertraline HCl release was studied. Spherical microspheres with a mean diameter of 21 to 26 Âµm loaded with 24.6 â€" 38.2% were produced. The in vitro drug release was shown to be depend on polymer molecular weight and also on the drug loading. Differential scanning calorimetry (DSC) was employed to investigate the physical state of sertraline HCl inside the microspheres and stability and polymer interaction study were performed in solution. Key words: Sertraline HCl , Microspheres , PLGA polymer